STAG2 loss amplifies EWS-FLI1-driven microsatellite enhancer activity promoting Ewing sarcoma aggressiveness - Sanjana Eyunni; Shih-Chun Chu; Mary L. Guan; Michaela Louw; Eleanor Young; Sandra E. Carson; Jianhui Gong; Marcin Cieslik; Arul M. Chinnaiyan; Abhijit Parolia (Proceedings of the National Academy of Sciences, 2026)
Ewing sarcoma is driven by chromosomal translocations that fuse a FET RNA-binding protein to an ETS transcription factor, most commonly generating the EWS-FLI1 fusion oncoprotein. EWS-FLI1 engages GGAA microsatellite repeats to form de novo enhancers that activate oncogenic transcriptional programs essential for tumorigenesis. In addition to this truncal driver, recurrent loss-of-function alterations in the cohesin subunit STAG2 occur in approximately 10 to 15% of Ewing sarcomas and are associated with adverse clinical outcomes. However, how STAG2 loss reshapes EWS-FLI1 chromatin engagement and transcriptional output remains poorly understood. Here, using genetic STAG2 loss-of-function models combined with integrative multiomic profiling, we demonstrate that STAG2–cohesin deficiency reprograms the EWS-FLI1 chromatin landscape by altering its binding at GGAA-microsatellite enhancers. Despite increased EWS-FLI1 protein abundance, STAG2 loss eliminates over 40% of EWS-FLI1 binding sites, predominantly at enhancers containing short (1–4) GGAA repeats, while concurrently increasing binding at multimeric enhancers with ≥5 GGAA-repeat motifs. These reprogrammed sites show changes in both chromatin accessibility and H3K27ac, leading to selective amplification of EWS-FLI1 activity at multimeric microsatellite enhancers. By integrating Hi-C chromatin interaction maps with altered EWS-FLI1 occupancy, we define distinct monomeric and multimeric GGAA enhancer–driven transcriptional gene signatures and demonstrate that STAG2 loss selectively augments the multimeric transcriptional program. Consistently, the long GGAA microsatellite-activated gene signature is enriched in patient tumors with aggressive clinical features and deleterious STAG2 alterations. Together, these findings reveal that STAG2 loss reprograms, rather than globally attenuates, EWS-FLI1 function, amplifying a high-risk oncogenic transcriptional state in Ewing sarcoma.